2020
DOI: 10.1186/s12872-020-01550-w
|View full text |Cite
|
Sign up to set email alerts
|

Incremental prognostic value of aortic stiffness in addition to myocardial ischemia by cardiac magnetic resonance imaging

Abstract: Background: Aortic stiffness is an independent predictor of cardiovascular (CV) events and mortality. However, no data exists for the prognosis of combined aortic stiffness and myocardial ischemia. Using cardiac magnetic resonance (CMR) imaging, we assessed the association of aortic stiffness by pulse wave velocity (PWV), myocardial ischemia, and CV events in patients with known or suspected coronary artery disease (CAD). Methods: Velocity-encoded CMR was performed in 520 patients who had undergone adenosine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
14
0
2
Order By: Relevance
“…Increased aortic stiffness was shown to have prognostic significance in healthy subjects and patients who had cardiovascular diseases, including CAD and non-ischemic cardiomyopathy such as hypertrophic cardiomyopathy [3] , [4] , [5] , [35] . A few studies demonstrated the prognostic value of aortic stiffness assessed by CMR for patients with stable CAD or post STEMI [36] , [37] . However, research focusing on the prognostic value of combined aortic stiffness and LGE is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Increased aortic stiffness was shown to have prognostic significance in healthy subjects and patients who had cardiovascular diseases, including CAD and non-ischemic cardiomyopathy such as hypertrophic cardiomyopathy [3] , [4] , [5] , [35] . A few studies demonstrated the prognostic value of aortic stiffness assessed by CMR for patients with stable CAD or post STEMI [36] , [37] . However, research focusing on the prognostic value of combined aortic stiffness and LGE is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Kaolawanich et al [60] investigated 520 patients who underwent adenosine stress cardiac magnetic resonance (CMR) and demonstrated that aortic PWV measured by CMR had incremental prognostic value to CMR results in the prediction of cardiovascular (CV) events during the median follow-up period of 46.5 months. In that study, patients with a higher PWV and positive ischemia on CMR had a significantly higher event rate compared to those with a lower PWV and negative ischemia (HR [hazard ratio], 8.94; p < 0.001).…”
Section: Incremental Prognostic Value Of the Measures Of Arterial Sti...mentioning
confidence: 99%
“…Studies showing incremental prognostic value of the measures of arterial stiffness are summarized in Table 1 (Ref. [24,[60][61][62][63][64][65][66][67][69][70][71]).…”
Section: Incremental Prognostic Value Of the Measures Of Arterial Sti...mentioning
confidence: 99%
“…Moreover, the predictive values of coronary flow reserve (as assessed by CMR) and stress perfusion CMR for major adverse cardiovascular events were comparable in patients with known CAD [ 46 ]. Adding aortic stiffness (as expressed by pulse wave velocity) to stress CMR could improve prediction of mortality, acute coronary syndrome, heart failure, need for coronary revascularization and stroke [ 47 ]. Furthermore, it has been suggested that the implementation of a score combining clinical (age, sex, diabetes mellitus and left ventricular ejection fraction) and stress CMR data (ischemic burden defined as the number of segments with stress-induced perfusion defects) could predict the risk of long-term all-cause mortality in patients with known or suspected CAD [ 48 ].…”
Section: Role Of Cmr In the Risk Stratification Of Patients With Cadmentioning
confidence: 99%